DESAIN MODEL PEMBELAJARAN DENGAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DAN PENDEKATAN ILMIAH TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA MATERI PROGRAM LINEAR DI KELAS XI SMA NEGERI 1 SUNGGAL - Pernando, Ivan (Jurnal Visi Eksakta, 2025)
This research uses quasi-experimental research. The population in this study were students of Class XI MIPA in SMA Negeri 1 Sunggal T.P. 2019/2020. This study aims to make it easier for students to achieve learning objectives in understanding the concepts and solving linear program problems with the Think Pair Share (TPS) type cooperative model and the scientific approach. The results showed that the design of the learning model that had been designed was good to use. The tcount value for the problem solving test is 5.0350 while the ttable = 1.667 it means tcount> ttable, means accepted or rejected, so it is concluded that learning with a cooperative model of think pair share type is better than the scientific approach to solving linear program problems in Class XI SMA Negeri 1 Sunggal T.P. 2019/2020.